Islamic Religious Education Subject to Strengthen Harmonization in National Life: A Case at a Multicultural School - Mukani Mukani (Postgraduate Program, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aimed at describing the portrait of the multicultural school in SMAN (State Senior High School) 1 Jombang, Indonesia, and explain the role of Islamic Education teachers in strengthening the character of students through multicultural-based Islamic religious learning at SMAN 1 Jombang, Indonesia. This study employed a qualitative descriptive research design with data collecting instruments used were interviews, observation, and documentation. The research was conducted from August 2017 to January 2018. The result of this study indicates that SMAN 1 Jombang is a multicultural school because of the different religious backgrounds embraced by school members. Judging from the origin of the tribe, the school members of the SMAN 1 Jombang come from different tribes. The conclusion of this study shows the various roles of Islamic religious education teachers in preventive efforts to manage multicultural into positive energy for advancing SMAN 1 Jombang.